An Analysis of Illocutionary Acts By Detective Hercule Poirot in the Movie Dialogue Entitled “Murder On The Orient Express” - Nurul Intan Sari (JELLE : Journal Of English Literature, Linguistics, and Education, 2021)
The research questions consisted of (1) What types of Illocutionary acts performed by Hercule Poirot in the movie entitled Murder on The Orient Express, (2) What are the functions of Illocutionary acts were performed by Hercule Poirot in the movie entitled Murder on The Orient Express. The research utilized the speech act theories type from Searle (1976) and the functions from Leech (2016) in analyzing the data.The data analysis was performed by categorizing the data based on Searle’s types which consist of Assertive, directive, commissive, expressive, and declarative. Each category was thoroughly observed to find the answer from the problem of the study. The final step was presenting the data and making conclusion in reference to the findings of the research. The research findings show that the types of illocutionary acts found in dialogue performed by Hercule Poirot consist of assertives, directives, commissives and expressive. Related to the problems of the study, functions of illocutionary acts found by the researcher are collaborative, competitive, convivial and conflictive.